Inflation in a monetary union - Carlberg, Michael (Berlin ; New York : Springer, 2002)
This book discusses the effects of money growth and output on infation. It also studies the causes and cures of inflation in a monetary union.
Includes bibliographical references (p. [295]-301) and index.
oif 21/02/14
Loan
Keywords: Inflation (Finance) -- Europe; Inflation (Finance) -- United States; Inflation (Finance) -- Mathematical models; Monetary unions -- Europe